Synthetic reactive dye wastewater treatment by using nano-membrane filtration - Rashidi, H.R.; Sulaiman, N.M.N.; Hashim, N.A.; Hassan, C.R.C.; Ramli, M.R. (2015)
The batik industry is considered to be one of the largest textile cottage industries in the Southeast Asian region. Batik processing utilizes wax as a physical resistant and consumes a large amount of water during dyeing, fixing, and washing process; thus, generating harmful wastewater including dye, wax, and other auxiliaries. Respectively, an efficient wastewater treatment method is deemed necessary to meet legal emission standards. In this study, application of polyamide nano-membrane to remove dyes was evaluated for five different fiber reactive dyes' wastewater, namely reactive blue 15, reactive red 194, reactive yellow 145, reactive black 5, and reactive orange 16. The discussed dyes were tested in low concentration (16 mg/l) during a 60 min filtration process. The efficiency of filtration was calculated based on pre-process and post-process analytical experiments. The flux for all the samples ranged between 7.8 and 9.2 ml/cm(2 )s. The permeate pH value of the samples was observed to slightly increase, within a range of 6.4-7.1. Conductivity measurements for the samples indicated dramatic reduction for each sample dye solution compared to the sample from the feed to permeate during the filtration runs. Chemical oxygen demand value in the permeate samples was reduced to zero, representing a dye removal efficiency of more than 90, thus successfully meeting the environmental legal standard.